Parental anxiety, child anxiety and father-child interactons : a longitudinal, multi-method investigation - Errity, Darina Elizabeth (Trinity College (Dublin, Ireland). School of Psychology, 2014)
Childhood anxiety represents a serious mental health concern, and there is a great need to identify risk factors influencing both its development and maintenance in order to design effective therapeutic interventions. Evidence suggests that parental behaviour may be one such risk factor; specifically, parental control and to a lesser extent, rejection. To date, however, methodological inconsistencies, failure to consider parental anxiety and reliance on cross-sectional design have limited the conclusions that can be drawn. Furthermore, as in many areas of developmental research, the role of fathers has been grossly underrepresented. This thesis thus sought to explore the role of paternal anxiety and paternal behaviour with respect to childhood anxiety.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin